Yusuf Al-Qardawi’s Thoughts On Ihtikar - Mardiatul Hasanah; S Sari (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2023)
The purpose of this research is (1) to find out Yusuf al-Qardawi's thoughts about ihtikar (2) to find out the right solution to overcome ihtikar. The research conducted was library research using qualitative methods. The data used are primary and secondary data. The data collection technique is by prioritizing works that have been tested for their truth. The results of the study show that (1) Yusuf al-Qardawi's thoughts on ihtikar are withholding goods from circulation in the market so that their prices rise, for all types of goods needed by humans. There is no consensus or disagreement from the fiqh scholars regarding the duration of hoarding. (2) the solution to overcoming ihtikar is that ihtikar does not need to occur in the world of commerce because a business that causes a lot of harm to the community also causes a hoarding of goods which causes a shortage of goods on the market. To the government (relevant agencies) in the case of ihtikar perpetrators to carry out intensive monitoring of existing forms of business in the community and take firm action against ihtikar perpetrators by imposing ihtikar punishments on them. And it is hoped that all people will avoid the need for ihtikar which has harmed many people.